Comparative Analysis of Strategies for Innovative Development of the Fuel and Energy Complex: The Experience of the EU Countries - Zholamanova, Makpal; Nurmukhametov, Nurbakhyt; Tolmachev, Mikhail; Sarsen, Kassymkhan; Amerkhanova, Altyn (International Journal of Energy Economics and Policy, 2023)
Most European countries do not have large reserves of natural resources and depend on imported energy resources. In this regard, the government of the European Union has approved a new energy policy aimed at developing a “green” economy and combating dependence on non-renewable resources. Currently, the European Union is a leader in the development of renewable energy sources. Many states have achieved success in this industry, their experience can be used in other countries where alternative energy is not so widespread. This study analyzes and compares existing strategies for the innovative development of the fuel and energy complex of EU member states. The process of formation of the EU energy policy and its distinctive features were studied. The example of Italy, Germany, Poland, Spain, and Finland was used to study in detail the impact of the new energy policy approved by the EU government. The prospects for the introduction of alternative energy sources in the geographical and climatic conditions of Kazakhstan have been assessed. Synthesizing the information obtained, a list of tips for the successful development of alternative energy in the Republic of Kazakhstan was proposed.